1999
DOI: 10.1159/000025654
|View full text |Cite
|
Sign up to set email alerts
|

MDR1 Gene Expression in Normal and Atherosclerotic Human Arteries<footref rid="foot01"><sup>1</sup></footref>

Abstract: Recent studies have shown that a membrane p-glycoprotein, encoded by MDR1 gene, is involved in the transport of free cholesterol from the plasma membrane to endoplasmic reticulum, the site of cholesterol esterification by acyl-CoA:cholesterol acyltransferase (ACAT). Moreover, results deriving from our previous studies have shown that the rate of cell proliferation was positively correlated with cholesteryl ester levels as well as with ACAT and MDR1 gene expression. In this study, lipid content and the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(19 reference statements)
0
18
0
Order By: Relevance
“…Lown et al (1997) found no change in age in intestinal P-gp expression in 25 renal patients between 21 and 67 years of age, whereas Batetta et al (1999) found that MDR1 mRNA expression was increased in the atherosclerotic plaques of elderly subjects.…”
mentioning
confidence: 94%
“…Lown et al (1997) found no change in age in intestinal P-gp expression in 25 renal patients between 21 and 67 years of age, whereas Batetta et al (1999) found that MDR1 mRNA expression was increased in the atherosclerotic plaques of elderly subjects.…”
mentioning
confidence: 94%
“…It is well known that CE accumulation is mainly due to two independent processes: the conversion of free cholesterol (FC) into CEs by acyl-CoA-cholesterol transferase 1 (ACAT-1) and the degradation of CEs into FC and free fatty acids by the neutral cholesterol ester hydrolase (n-CEH). We have previously reported that CEs play a critical role in the control of the G1/S transition of the human VSMC cell cycle [15,16,17,18]: thymidine incorporation into DNA in serum-stimulated VSMCs was preceded by an increase in the rate of cholesterol esterification. CE inhibitors were able to prevent proliferation of VSMCs by blocking the progression of the cell cycle from the G1 to the S phase.…”
Section: Introductionmentioning
confidence: 99%
“…[9] The expression of P-gp, a transport protein dependent on ATP, is decreased when there is a single nucleotide polymorphism in 26 th exon of the MDR-1 gene. [10][11][12] Furthermore, the evidence of previous studies has shown that cholesterol ester level binding to MDR-1 gene expression is positively correlated with cellular proliferation. [10] Besides it has been shown that MDR-1 was observed in pathologies that affect the vessel wall such as atherosclerosis.…”
mentioning
confidence: 99%
“…[10][11][12] Furthermore, the evidence of previous studies has shown that cholesterol ester level binding to MDR-1 gene expression is positively correlated with cellular proliferation. [10] Besides it has been shown that MDR-1 was observed in pathologies that affect the vessel wall such as atherosclerosis. [10] In this study we aimed to investigate the relationship between MDR-1 gene polymorphism and AAA.…”
mentioning
confidence: 99%
See 1 more Smart Citation